2021
DOI: 10.1037/aca0000297
|View full text |Cite
|
Sign up to set email alerts
|

A novel coding scheme for assessing responses in divergent thinking: An embodied approach.

Abstract: In this study, we devised a novel coding scheme for responses generated in a divergent thinking (DT) task. Based on considerations from behavioral and neurocognitive research from an embodied perspective, our scheme aims to capture dimensions of simulations of action or the body. In an exploratory investigation, we applied our novel coding scheme to analyze responses from a previously published dataset of DT responses. We show that (a) these dimensions are reliably coded by naïve raters and that (b) individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Future research should take these possible qualitative differences in underlying processes into account. As a starting point, the recently developed coding scheme of Matheson and Kenett ( 2020 ) could be useful, which defines six dimensions (i.e., analogy vs. action, whole vs. parts, same vs. different, concrete vs. abstract, novel vs. familiar, and towards vs. away) to characterise the strategies used by participants to generate divergent thinking responses.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should take these possible qualitative differences in underlying processes into account. As a starting point, the recently developed coding scheme of Matheson and Kenett ( 2020 ) could be useful, which defines six dimensions (i.e., analogy vs. action, whole vs. parts, same vs. different, concrete vs. abstract, novel vs. familiar, and towards vs. away) to characterise the strategies used by participants to generate divergent thinking responses.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that this is only the tip of the iceberg and that there are more cues involved in creative processes still to be exposed. For example, Matheson and Kenett (2021) demonstrated how different motion-related strategies impact AUT responses (see also Gilhooly et al 2007). In a recent study of theirs, Sargent et al (2023) empirically demonstrated how environmental context and body posture impact performance on the AUT.…”
Section: Discussionmentioning
confidence: 99%
“…This data is in line with studies of episodic future thinking (Schacter et al, 2017; see also Schacter et al, 2012), which stress the role of an individual's ability to recollect past personal experiences. The authors suggested that sensorimotor re-enactment and mental exploration of outcomes of such actions (Matheson and Kenett, 2021; see also Jeannerod, 2001;Witt and Proffitt, 2008) may be an effective strategy to come up with novel alternative uses.…”
Section: The Alternative Interpretations Of the Autmentioning
confidence: 99%